Intelligent control technique of FES-assisted elliptical stepping exercise in hemiplegic rehabilitation / Saiful Zaimy Yahaya - Yahaya, Saiful Zaimy (2018)
Rehabilitation exercise has been regarded as one of the promising methods to regain functions for people suffering from hemiplegic. In recent decades, rehabilitation exercise with the use of functional electrical stimulation (FES) has been the focus among researchers with a variety of exercise techniques involved. Rehabilitation exercise with the use of wheelchair accessed elliptical stepping ergometer has not much been explored especially on the practical adaptation of the users and control technique for FES. The studies in this research aimed to propose a new design of elliptical stepping ergometer and enhance the performance of FES-assisted elliptical stepping exercise through the design and implementation of intelligent control technique. The studies started with the design of the elliptical stepping ergometer that allowed for wheelchair access and incorporates between FES and voluntary movement in actuating the exercise movement. This involves the design concept, development of a model and a prototype. The complete system model of the FES-assisted elliptical stepping exercise was validated via an experimental work with the prototype. In the control technique design, early investigations was done on the performance of an FES-assisted elliptical stepping exercise controlled by proportional-integral-derivative (PID) controller. The control technique was further improved using the fuzzy logic controller (FLC). The FLC was proven to have better performance compared to PID. Further investigations was then carried out to improve the ability of FLC in enhancing the FES-assisted elliptical stepping exercise performance. A stimulation shifting technique was introduced to reduce the cadence error at the beginning of stimulation cycle due to delay in muscle response. Two techniques of stimulation shifting were developed that manipulated the stimulation pulse width and cadence error to enhance the FLC control action. A constant pattern of the FES signal was also taken into consideration in the control technique design. This control technique was realized by the implementation of the cycle-to-cycle control. In the implementation, two new FLC inputs were introduced to suit the movement nature of elliptical stepping. The inputs were the cadence error at the previous movement cycle maximum points and time per cycle error of the previous movement cycle. The FLC rules were also modified to generate suitable control action as a respond to the FLC inputs. Taking into consideration that an external assist via energy storage mechanism may improve the performance of FES-assisted elliptical stepping exercise, the installation of two types of energy storage mechanism which are linear extension spring and constant force spring were carried out. These techniques allowed the spring to store the excess force at the end of a movement cycle and release it as an assist force at the start of the next movement cycle. The FLC cycle-to-cycle control was maintained as the control technique. In the all mentioned control techniques, an optimization technique based on GA and PSO were used to optimize the parameters involved. Based on the analysis, all control techniques were significantly enhanced the performance of the FES-assisted elliptical stepping exercise. The best performance was shown by FLC stimulation shifting where it was recorded with 1.998 RPM of overall average cadence error. All in all, this indicated the potential use of FES-assisted elliptical stepping exercise with the designed control techniques as methods in hemiplegic rehabilitation.